2016
DOI: 10.1186/s12866-016-0867-4
|View full text |Cite
|
Sign up to set email alerts
|

Fucosyllactose and L-fucose utilization of infant Bifidobacterium longum and Bifidobacterium kashiwanohense

Abstract: BackgroundHuman milk oligosaccharides (HMOs) are one of the major glycan source of the infant gut microbiota. The two species that predominate the infant bifidobacteria community, Bifidobacterium longum subsp. infantis and Bifidobacterium bifidum, possess an arsenal of enzymes including α-fucosidases, sialidases, and β-galactosidases to metabolise HMOs. Recently bifidobacteria were obtained from the stool of six month old Kenyan infants including species such as Bifidobacterium kashiwanohense, and Bifidobacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
189
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(206 citation statements)
references
References 46 publications
14
189
1
2
Order By: Relevance
“…Interestingly, 2´FL application to mice increases the levels of Barnesiella indicating that in mice 2´FL metabolization is a possible route to generate metabolites which could cross the intestinal barrier and accumulate in the circulation. In this context, the consumption of 2´FL by microbial species from the genera Barnesiella, Bifidobacterium , and Bacteroides may lead to the production of smaller molecules such as lactose, fucose or organic acids such as butyrate, acetate, or lactate . With regard to our experiments, we speculate that 13 C‐enrichment may reflect the presence of fucose itself or a fucose‐derived metabolite since the fucose moiety of 2´FL carried the 13 C‐labeling at the C 1 ‐atom and 2´FL itself could not pass the blood–brain barrier as has been shown by i.v.…”
Section: Discussionmentioning
confidence: 82%
“…Interestingly, 2´FL application to mice increases the levels of Barnesiella indicating that in mice 2´FL metabolization is a possible route to generate metabolites which could cross the intestinal barrier and accumulate in the circulation. In this context, the consumption of 2´FL by microbial species from the genera Barnesiella, Bifidobacterium , and Bacteroides may lead to the production of smaller molecules such as lactose, fucose or organic acids such as butyrate, acetate, or lactate . With regard to our experiments, we speculate that 13 C‐enrichment may reflect the presence of fucose itself or a fucose‐derived metabolite since the fucose moiety of 2´FL carried the 13 C‐labeling at the C 1 ‐atom and 2´FL itself could not pass the blood–brain barrier as has been shown by i.v.…”
Section: Discussionmentioning
confidence: 82%
“…infantis BRS8-2 and TPY1201 are known to degrade 2 FL, 3FL, 3 SL and LNnT, while B. longum subsp. infantis DSM 20088 has been shown to utilise 2 FL, 3FL, and LNnT [68]. Therefore, it is likely that the prebiotic effect associated with GMOs may extend to other strains.…”
Section: Prebiotic Effects Of Gmomentioning
confidence: 99%
“…The genome of B. infantis ATCC 15697 possesses two gene clusters containing genes that are similar to a fucose pathway involving nonphosphorylated intermediates that have been previously described in C. jejuni and Xanthomonas campestris (Sela et al 2012, Yew et al 2006). Bunesova et al (2016) showed that fermentation end products lactate, acetate, and 1,2-propanediol were formed during growth of B. infantis and Bifidobacterium longum subsp. suis on L-fucose.…”
Section: Molecular Mechanisms Of Utilization Of Human Milk Oligosacchmentioning
confidence: 99%
“…suis on L-fucose. This work proposed an L-fucose pathway similar to X. campestris and C. jejuni involving the formation of nonphosphorylated intermediates (Bunesova et al 2016). …”
Section: Molecular Mechanisms Of Utilization Of Human Milk Oligosacchmentioning
confidence: 99%